1989
DOI: 10.1038/341149a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of brain-derived neurotrophic factor

Abstract: During the development of the vertebrate nervous system, many neurons depend for survival on interactions with their target cells. Specific proteins are thought to be released by the target cells and to play an essential role in these interactions. So far, only one such protein, nerve growth factor, has been fully characterized. This has been possible because of the extraordinarily (and unexplained) large quantities of this protein in some adult tissues that are of no relevance to the developing nervous system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
604
2
7

Year Published

1990
1990
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,403 publications
(627 citation statements)
references
References 26 publications
7
604
2
7
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) (Barde et al, 1982;Leibrock et al, 1989) (Nakagawara et al, 1994). In this study we have investigated the mRNA expression profile of the third member of the neurotrophin receptor tyrosine kinase family, trkC, a receptor for neurotrophin-3 (NT-3) (Lamballe et al, 1991) which is involved in the survival of subpopulations of neural crest and placodederived sensory neurons (Ernfors et al, 1994 (Shelton et al, 1995) which was identical to that of our clone in the transmembrane region.…”
mentioning
confidence: 65%
“…Brain-derived neurotrophic factor (BDNF) (Barde et al, 1982;Leibrock et al, 1989) (Nakagawara et al, 1994). In this study we have investigated the mRNA expression profile of the third member of the neurotrophin receptor tyrosine kinase family, trkC, a receptor for neurotrophin-3 (NT-3) (Lamballe et al, 1991) which is involved in the survival of subpopulations of neural crest and placodederived sensory neurons (Ernfors et al, 1994 (Shelton et al, 1995) which was identical to that of our clone in the transmembrane region.…”
mentioning
confidence: 65%
“…Various evidences point to intimate interactions within these two transduction systems. Indeed, NGF and BDNF (brain-derived neurotrophin factor; Leibrock et al, 1989) have been shown to induce cAMP response in PC12 cells (Knipper et al, 1993) while cAMP has been shown to activate the MAP (mitogen-activated protein) kinase cascade in the same cells (Frodin et al, 1994). In addition, treatment of PC12 cells with PACAP, a adenylyl cyclase-coupled agent, has been reported to induce neurite outgrowth in manner similar to NGF (Deutsch and Sun, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Levi-Montalcini and coworkers discovered nerve growth factor (NGF), the first member of the family, over forty years ago (for review see [1]). Since the cDNA structure coding for the precursor of NGF (proNGF) was reported [2], four other members of the family have been identified and their cDNAs cloned: brain-derived neurotrophic factor (BDNF) [3], neurotrophin-3 (NT3) [4,5], neurotrophin-4/5 (NT-4/5) [6] and neurotrophin-6 (NT-6) [7]. Sequence data predict that all neurotrophins are generated from 31 35 kDa precursors that contain at their N-termini, hydrophobic signal peptides followed by proregions containing sequences of contiguous basic amino acids.…”
Section: Introductionmentioning
confidence: 99%